(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study found out that at the beginning of every semester, tutors sell course handouts which are examination-oriented with a lot of past questions to the pre-service teacher on which the latter becomes over-reliant for their preparation towards examination. These factors, the study observed, have made tutors pedagogy tilted from TPCK deliveries to examination preparation activities with little or no emphasis on equipping the pre-service teacher with lesson facilitation and class management strategies. This is gradually killing the college tutors’ innovations in the Lecture Theatres which reflects on a statistically significant difference in the impact of end of semester examination among year 1, year 2 and year 3 English language specialism students. It was concluded that UCC administered End of semester examination as a high-stakes test influences teaching and learning negatively as pre-service teachers focus more on passing examination than equipping themselves with pedagogical practices for the delivery of the SBC Curriculum in the basic schools of Ghana. It was therefore recommended that UCC should consider integrating pedagogy with content questions to promote positive or beneficial impact on teaching and learning. Also, principals of UCC affiliated colleges should put measures in place to strengthen Teacher Professional Learning Sessions (TPLS) in their individual colleges, for it provides a fine opportunity for staff and pre-service teacher development